Pengaruh Audit Tenure, Fee Audit, dan Ukuran Perusahaan Terhadap Kualitas Audit - Davina Christophia Angelica; Rousilita Suhendah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study was conducted to determine the effect of audit tenure, audit fees, and company size on audit quality in financial industry companies, particularly in the banking sub-sector. This study used purposive sampling, with a sample size of 95 observations from 19 financial sub-sector companies listed on the Indonesia Stock Exchange (IDX) for 5 years from 2019 to 2023. The data analysis method used was logistic regression analysis with the help of Eviews 13 software. The results of this study indicate that audit tenure and company size have a negative effect on audit quality. Meanwhile, audit fees have a positive effect on audit quality.